2022
DOI: 10.1093/ndt/gfac093.001
|View full text |Cite
|
Sign up to set email alerts
|

FC001: Humoral Response to Third Dose of Sars-Cov-2 Vaccines in the CKD Spectrum: The Sencovac Study

Abstract: BACKGROUND AND AIMS There is incomplete information on the impact of a third dose of the SARS-CoV-2 vaccine in advance chronic kidney disease (CKD). The aim of the present analysis was to evaluate the kinetics of humoral response in the CKD spectrum (KT, HD, PD and ND-CKD) 6 months after completing the initial vaccine schedule. Some patients of each group received a third dose before 6 months, providing a pragmatic insight into real-world responses to different vaccine schedules in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…Patients with non-dialysis kidney disease and on dialysis presented good antibody response to vaccination, especially after third and fourth doses. Kidney transplant recipients presented suboptimal response after all doses, with persistent negative seroconversion after third and fourth doses [58 ▪ ]. Similar findings were observed in a Dutch cohort comparing seroconversion in non-dialysis advanced kidney disease, dialysis patients and controls.…”
Section: Covid-19 Vaccination; Humoral Responses In Chronic Kidney Di...supporting
confidence: 82%
See 1 more Smart Citation
“…Patients with non-dialysis kidney disease and on dialysis presented good antibody response to vaccination, especially after third and fourth doses. Kidney transplant recipients presented suboptimal response after all doses, with persistent negative seroconversion after third and fourth doses [58 ▪ ]. Similar findings were observed in a Dutch cohort comparing seroconversion in non-dialysis advanced kidney disease, dialysis patients and controls.…”
Section: Covid-19 Vaccination; Humoral Responses In Chronic Kidney Di...supporting
confidence: 82%
“…Immune response to SARS-CoV-2 vaccination across the kidney disease spectrum (CKD, dialysis and kidney transplant) has been assessed in two recent prospective studies [57 ▪ ,58 ▪ ]. The SENCOVAC study assessed humoral responses (antispike protein IgG antibodies) in nondialysis kidney disease, haemodialysis and transplant 28 days, 3 months, 6 months and 12 months after vaccination in a Spanish cohort.…”
Section: Covid-19 Vaccination; Humoral Responses In Chronic Kidney Di...mentioning
confidence: 99%
“…Low serum anti-spike concentrations have been associated with an increased risk of break-through infections in hemodialysis patients 17, 18 . We detected high surrogate NAb titers against the original Wuhan-strain in all our patients although absolute NAb values were significantly decreasing in SARS-CoV-2 naïve patients during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, health authorities emphasize that vaccination approaches against COVID‐19 should be a priority in CKD and kidney recipients. However, the efficacy of COVID‐19 vaccines in immunocompromised kidney transplant patients was found to be significantly lower than in other populations 5,6 . At the beginning of the COVID‐19 pandemic, it was not understood how effective the vaccines were in these patient groups, as the phase III studies against COVID‐19 did not include CKD, dialysis, or kidney recipients and focused only on normal individuals.…”
Section: Introductionmentioning
confidence: 99%
“…With these measures, it has been clearly demonstrated that the COVID‐19 disease can be controlled after the emergence of different effective and safe vaccines in the normal population 3,4 . So far, messenger RNA (mRNA)‐based COVID‐19 vaccines have proven to be the most protective vaccine type against COVID‐19 disease in the normal population and in different chronic kidney diseases (CKDs) 3,5–7 . CKD and kidney transplantation are important independent risk factors for severe COVID‐19 disease 8–10 .…”
Section: Introductionmentioning
confidence: 99%